Treatment of Wastewater from Rubber Industry Using Calcium Carbide Residue Adsorbent and Hybrid Membrane UF – RO - Susi Susanti; Subriyer Nasir; Hermansyah Hermansyah; Agung Mataram (Sriwijaya Journal of Environment, 2019)
Hybrid UF – RO membrane technology is one of the new technologies of separation wastewater from the rubber industry to decrease turbidity and heavy metal contents such as iron and zinc. This technology is being used to replace the conventional installation process of wastewater treatment. Processing wastewater treatment from the rubber industry with the hybrid UF – RO membrane can produce permeate with quality standards, making it possible to be recycled as domestic water for water process in the industry. The technology of wastewater treatment from the rubber industry in this experiment involved the pre-treatment stage, using sand filter and adsorption using calcium carbide residue. The operating variables by flow rate into the UF and RO were 7 and 14 L.Min-1 and operation time were 15 to 90 minutes. The results of this study showed that the percentage reduced were 62.73% for turbidity, 83.28% for iron and 88.89% for zinc, respectively. Finally, it can be concluded that calcium carbide residue was potential to reduced turbidity and heavy metals such as iron and zinc from rubber industry wastewater.